Bacterial extracellular vesicles target different bacterial species, impairing cell division and diminishing their pathogenicity - Yu Kawagishi; Kazunori Murase; Anna Grebenshchikova; Junpei Iibushi; Chang Ma; Teresia M. Kimeu; Atsuko Minowa-Nozawa; Takashi Nozawa; Ichiro Nakagawa (Proceedings of the National Academy of Sciences, 2025)
Extracellular vesicles (EVs) produced by bacteria contain many bacterial-derived molecules, which play an important role in host interactions and as mediators of bacterial communication. However, the role of EVs in interspecies interactions and their physiological and ecological significance are not well understood. In this study, we found that Escherichia coli EVs inhibit the growth of group A Streptococcus (GAS; Streptococcus pyogenes ) by inducing defective cell division via the following processes. E. coli EVs first attach to the cell surface of GAS. In EV-attached GAS cells, multiple septa and Z-rings form in close proximity, which clearly differs from the typical cell division process. This is due to inhibition of peptidoglycan (PG) remodeling in the process after septum formation, in which the next cell division is initiated without completion of peripheral PG synthesis. Therefore, cell division proceeds while inducing cell elongation and cell separation failure, leading to growth inhibition. Furthermore, EV alters the expression of approximately 10% of all genes encoded on the GAS genome, and the diverse functions of these gene sets, which include replication, division, and metabolism, suggest that EVs have a variety of biological effects on the targeted bacterial cells. Notably, E. coli EVs significantly decreased the expression of genes involved in representative GAS virulence, such as slo , nga , and hasA , and also markedly attenuated the pathogenicity of GAS in mice. Our findings provide insight into the competitive functions of EVs between different bacterial species, expanding current knowledge on EV-mediated interspecies interactions.